Accurate steady-state modeling of capacitive-coupling interface of capacitive power transfer systems with cross-coupling. Issue 1 (7th March 2016) - Huang, Liang; Hu, Aiguo Patrick; Swain, Akshya K.; Su, Yugang
Abstract : Capacitive power transfer (CPT) technology can achieve wireless power transfer based on electric field coupling. However, practical CPT systems often have cross-coupling between coupling plates of the capacitive-coupling interface, which makes accurate system analysis and compensation design tedious and complicated. In this paper, an accurate steady-state equivalent circuit model of the capacitive-coupling interface with cross-coupling is established. The model includes a parallel input capacitor linked with a series output capacitor by an ideal transformer whose turns ratio reflects the extent of cross-coupling between the plates. Effects of coupling variation on the model are analyzed in detail. The model is used for primary and secondary tuning design to achieve the maximum power transfer of a CPT system with cross-coupling. The effectiveness of the proposed model is demonstrated by both simulations and experimental results.